Effect of Constituent Units, Type of Interflavan Bond, and Conformation on the Antioxidant Properties of Procyanidin Dimers: A Computational Outlook - Ana María Mendoza-Wilson; René Renato Balandrán-Quintana (Journal of Chemistry)
Procyanidin (PC) dimers are powerful antioxidants, abundant in plant tissues, and also bioavailable. However, the role of the molecular structure of PCs on their antioxidant properties is still a controversial and not fully understood issue that needs to be addressed in a more specific way. The objective of this study was to analyze the effect of the constituent units, type of interflavan bond, and conformation on the antioxidant properties of PC dimers including PB3, PB4, PB5, PB6, PB7, and PB8, using the density functional theory (DFT) computational method. The analysis was performed in function of parameters that allow determining the ability of the molecules to transfer or to capture electrons, among which the chemical potential, bond dissociation enthalpy (BDE), gap energy, Fukui indices, and charge distribution of HOMO-LUMO orbitals. The factors that showed the most notable effects on the antioxidant properties of the PC dimers were the type of interflavan bond and the conformation. The antioxidant ability of the dimers PB3 and PB4 containing the interflavan bond C4–C8, in their Compact conformation, was very similar to each other but greater than those of dimers PB5, PB6, PB7, and PB8 containing the C4–C6 interflavan bond. PB8 showed the lowest antioxidant ability.